Morbidity pattern and mortality of neonates admitted in a tertiary level teaching hospital in Bangladesh (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):159-62.The abstract of this article is available on the PubMed website